1967
DOI: 10.1530/jrf.0.0140081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thyroid Activity Upon Delayed Implantation of Blastocysts in the Rat

Abstract: The effects of l-thyroxine and of surgical thyroidectomy upon the survival of blastocysts have been studied in 200 albino rats. These rats were ovariectomized on the 3rd day of pregnancy, and maintained on progesterone in order to delay implantation. Delay of implantation was confirmed by laparotomy on the 8th day of pregnancy. Subsequent implantation was accomplished by giving 1 \ g=m\ g oestrone daily from the 9th day of pregnancy. At autopsy on the 14th day of pregnancy hyperthyroid rats and hypothyroid rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1968
1968
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…oviduct flushings in other experiments.) These findings are discussed in detail elsewhere (Holland et al 1967). Immediately above the bar graphs of Fig.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…oviduct flushings in other experiments.) These findings are discussed in detail elsewhere (Holland et al 1967). Immediately above the bar graphs of Fig.…”
Section: Resultsmentioning
confidence: 54%
“…The procedure for obtaining the delayed implantation of blastocysts has been described in detail elsewhere (Holland et al 1967). Briefly, it is based upon the method of Cochrane 8c Meyer (1957) and involves ovariectomy on Day 3 of pregnancy, daily injection of progesterone through Day 8, verification of delay by laparotomy on Day 8, and supplementing the progesterone with oestrone on Days 9 through 14 to obtain implantation and development of the blastocysts.…”
Section: Methodsmentioning
confidence: 99%
“…A daily dosage of 15 /¿g was highly effective and 8^g daily has also proved to be quite effective in counteracting progesterone deficiency. In earlier studies of delayed implantation, it was reported (Holland et al, 1967) (1956) reported that thyroid activity increases by 100% during normal oestrus as compared with di-oestrus in the rat, while Grosvenor & Turner (1958) reported that lactation may also produce a two-fold increase in thyroid secretion in the rat. Thyroxine secretion rate in the rat has been reported (Grosvenor & Turner, 1958) to be 1-24 to 1-75 µg/100 g body wt/day or about 2-8 to 4-0 /ig/day in rats of the size used in our experiments.…”
mentioning
confidence: 99%
“…Investigators have reported beneficial effects, disadvantageous effects and some have reported that it exerts no effect. Exam¬ ples of these investigations and possible reasons for the conflicting results were presented in an earlier publication (Holland, Dorsey, Harris & Johnson, 1967 (Holland et al, 1967) (Meyer & Nutting, 1964) of Days 3 to 8 rather than influencing the effectiveness of the oestrogen-dependent implanta¬ tion process (Prasad, Mohla & Rajalakshmi, 1969).…”
mentioning
confidence: 99%
See 1 more Smart Citation